QUALITATIVEANDQUANTITATIVESTUDYOFPHYTO-COMPOUND PRESENTINROOTSOFCLITORIATERNATEAUSING SPECTROSCOPYANDCHROMATOGRAPHICTECHNIQUES - SwatiSaxena; JankiPrasadRai (The Bioscan, 2025)
The present studywas undertaken to evaluate the phytochemical profile, thin-layer chromatographic (TLC) characteristics,andtotalphenolicandflavonoidcontentofrootextractsofClitoriaternatea.Successiveextraction was carriedout usingsolventsof increasingpolarity (hexane, chloroform, ethyl acetate, ethanol, anddistilled water).Theextractivevalues indicatedmaximumyieldwithaqueous (7.25%w/w) andethanolic(6.67%w/w) solvents, suggesting a predominance of polar constituents. Preliminaryphytochemical screening revealed the presence of flavonoids, phenols, proteins, carbohydrates, saponins, and diterpenes indifferent extracts, with flavonoidsbeingconsistentlydetectedinethylacetate,ethanol,andaqueousextracts.TLCanalysisconfirmedthe presenceofmultipleflavonoidcomponents,withethanolandethylacetateextractsshowingthehighestdiversity and quercetin-like compounds (Rf ≈ 0.63). Quantitative estimation demonstrated that the ethanolic extract contained thehighest phenolic (1.04mg/100mg) and flavonoid (1.65mg/100mg) content, followedby the aqueousextract(flavonoids:1.41mg/100mg).Thesefindingssuggest thatethanolisthemostefficientsolventfor extractingphenolicandflavonoidconstituentsfromClitoriaternatearoots,highlightingitspotential for further pharmacologicalandtherapeuticinvestigations